2014
DOI: 10.1038/srep05401
|View full text |Cite
|
Sign up to set email alerts
|

Triggered dynamics in a model of different fault creep regimes

Abstract: The study is focused on the effect of transient external force induced by a passing seismic wave on fault motion in different creep regimes. Displacement along the fault is represented by the movement of a spring-block model, whereby the uniform and oscillatory motion correspond to the fault dynamics in post-seismic and inter-seismic creep regime, respectively. The effect of the external force is introduced as a change of block acceleration in the form of a sine wave scaled by an exponential pulse. Model dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In the present paper, we study the cases of a simple fault and the paradigmatic two-block complex fault, made up of homogeneous or heterogeneous blocks. The block dynamics is provided by a version of the Burridge-Knopoff model supplied by the Dieterich-Ruina rate-and state-dependent friction law [50][51][52][53][54] . Note that the selection of friction law is an important point for the models where friction enters as a force term.…”
Section: Model Of Fault Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present paper, we study the cases of a simple fault and the paradigmatic two-block complex fault, made up of homogeneous or heterogeneous blocks. The block dynamics is provided by a version of the Burridge-Knopoff model supplied by the Dieterich-Ruina rate-and state-dependent friction law [50][51][52][53][54] . Note that the selection of friction law is an important point for the models where friction enters as a force term.…”
Section: Model Of Fault Dynamicsmentioning
confidence: 99%
“…Fig. 2(c), which may be appropriate to describe pre-seismic and post-seismic creep regimes 52 . Nevertheless, the regime of relaxation oscillations which we are interested in, can be found sufficiently away from criticality, see Fig.…”
Section: Model Of Fault Dynamicsmentioning
confidence: 99%
“…If, however, the critical Gruntfest number, the homoclinic point and the Hopf Point are known a priori, the forward model can generate the transient time series needed for the data assimilation step. However, as it is expected, in order for the present model to predict proper chaotic behaviour, the equations for the evolution of the internal variables need to be included [2,6]. This will allow the variation of the Gruntfest and the Lewis number, which is necessary for the transition between the different oscillatory modes [10].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of large earthquakes that generate on sometimes hundreds of kilometre-long faults has been, thus far, approached from a statistical and empirical angle. The reasons for using this approach are that the dynamics related to earthquake and fault motion are likely stochastic rather than deterministic in nature [1][2][3], thus making approaches that aim at physics-based forecasting of deterministic dynamics just part of the whole story. Unpredictability is an inherent part of such systems.…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to periodic parameter perturbations, Kostić et al showed that minor perturbation to the parameters such as the oscillation amplitudes and the angular frequencies are sufficient to change the original behavior, leading to the onset of chaos [12]. The effect of a transient periodic external force was introduced to describe the dynamic triggering impact of nearby or distant earthquakes [13].…”
Section: Introductionmentioning
confidence: 99%